Perilaku kekuatan fatigue paduan aluminium seri 2014 akibat proses termomekanikal aging - -, Sujita (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Desember 2008, 2012)
Aluminium alloy seri 2014 is material which is often used in industry. Because excellence of mechanic properties. But also have the weakness at properties of strength fatigue. Though fatigue strength is important parameter in desain, especially if application at condition of dinamic loading, so that need the treatment to improve it. Fatigue strength go together the micro structure and mode of failure of failure of effect of stress concentration. Aging treatment ordinary done not yet given the influence which even on the contrary. Inconsistence of fatigue strength alluminium alloy show the phenomenon which must be research instructing at repair of fatigue strength , so that need the advanced treatment in the form of termomechanical aging. The research conducted by using alluminium alloy series 2014 formed by specimen fatigue test of the size diameter 8 mm and long 87 mm relate at standart (ASTM E 513), continued treatment of termomechanical aging, tested the fatigue, and monitoring microstructure of change. By structure micro, the treatmentTMA have the effect which sicnificant to improvement of Alluminium alloy series 2104 fatigue strength. Generally entire process TMA improve of limit fatigue from specimen at condition early of limit fatigue 48.3 N / mm2 (48.3 MPA), mounting to become 50 until MPA, or mount 3.4 % until 44.9%. With the process of termomechanical aging TMA I, happened the increasing of cycle number equal to, 26.3 %, at treatment of TMA II go up equal to 62 % and 89.8% at process of TMA III, at maximal loading (180 Mpa).
Keywords: Alluminium alloy seri 2014, termomechanical aging, fatigue strength